2023
DOI: 10.3390/bs13070537
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Self-Efficacy and Perfectionism on Academic Procrastination among University Students in Pakistan

Abstract: This study aimed to evaluate the impact of self-efficacy and perfectionism on academic procrastination among university students and its differences among genders in Pakistan. It was hypothesized that self-efficacy and perfectionism would significantly impact academic procrastination and that there is a significant difference in students’ views concerning their gender. The sample comprised 405 university students, 104 male and 301 female. The study used the general self-efficacy scale, the multidimensional per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…This result is consistent with (Abood et al, 2020;Aniljose, Kerala & Aleesha, 2021;Sachitra & Bandara, 2017), which showed that there were differences in favor females. While disagreeing with (Ashraf et al, 2023;Baji, 2020;Turhan, Mwaura, 2020), which resulted in no gender differences in academic self-efficacy, the current results also differ from those (Fallen & Opstad, 2016;Jamil, 2018) because there are differences in favor of males. This could be because males often go out to play ball and electronic games outside the home with friends, and spend long periods outside the home, while at the same time, females stay at home to plan and complete academic tasks, as well as because of the nature of society's preference for males over females, which pushes females to show themselves their superiority and increase their self-confidence by completing academic work with the best performance.…”
Section: Variablecontrasting
confidence: 94%
See 1 more Smart Citation
“…This result is consistent with (Abood et al, 2020;Aniljose, Kerala & Aleesha, 2021;Sachitra & Bandara, 2017), which showed that there were differences in favor females. While disagreeing with (Ashraf et al, 2023;Baji, 2020;Turhan, Mwaura, 2020), which resulted in no gender differences in academic self-efficacy, the current results also differ from those (Fallen & Opstad, 2016;Jamil, 2018) because there are differences in favor of males. This could be because males often go out to play ball and electronic games outside the home with friends, and spend long periods outside the home, while at the same time, females stay at home to plan and complete academic tasks, as well as because of the nature of society's preference for males over females, which pushes females to show themselves their superiority and increase their self-confidence by completing academic work with the best performance.…”
Section: Variablecontrasting
confidence: 94%
“…It agrees with Aniljose et al (2021); Mandap, 2016). Whereas disagree with Ashraf et al (2023), who showed no differences due to gender in academic placement. The existence of differences in academic procrastination in favor of males can be explained by considering the personality traits and social roles expected of both males and females, as males are prepared from the point of view of parents to assume responsibility and build an independent family, which increases the pressure on the student.…”
Section: Variablementioning
confidence: 78%
“…It has been stated that procrastination may include the decreased ability to be present ( Glick et al, 2014 ), which is a central part of psychological flexibility ( Hayes et al, 2006 ). Previous studies have also shown that, for example, perfectionism, including a very critical assessment of one’s own behavior and performance, which is evident among university students, is related to procrastination ( Çapan, 2010 ; Ashraf et al, 2023 ). Psychological flexibility skills help one to accept difficult emotions and thoughts about oneself and can help to develop a less critical and more lenient attitude towards oneself, living life according to one’s own values instead of avoidance ( Hayes, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the measurement of academic procrastination at home and abroad, there also exist mature scales. Solomon et al have compiled the procrastination assessment scale, which is the most widely used [54]. Huang Qingshuang et al (2019) [3] combined this scale with the online learning environment as well as the learning activities, in order to revise the academic procrastination scale with respect to the online learning environment, including the degree of academic procrastination, academic procrastination brought about by the impact of procrastination, and procrastination to change the intention of the three dimensions.…”
Section: Academic Procrastination Scalementioning
confidence: 99%